Pelatihan Pengembangan Soal Evaluasi Berbasis Argumentasi Bagi Guru Kimia di Kabupaten dan Kota Mojokerto - Rusmini, Rusmini; Rudiana Agustini; Muchlis, Muchlis; Harun Nasrudin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
An initial survey showed that some chemistry teachers at the MGMP of Mojokerto Regency and City had never attended argumentation skills training. Argumentation skills are important to practice as an effort to improve critical thinking skills, improve understanding and problem solving. This activity aims to improve the understanding and skills of chemistry teachers in Mojokerto in developing argumentation-based evaluation questions. This activity was carried out in two sessions through six stages of activities starting from preparation, training, monitoring, implementation, evaluation, and appreciation stages. The results showed that the development of teachers' understanding related to argumentation skills was analyzed using the N-Gain score and the majority were in the moderate group. The results of the question development also showed an increase in the level of argumentation skills. The response questionnaire showed that all teachers supported this PKM activity and the activity had been 100% implemented. This activity is expected to be one of the triggers for teachers to make their students more critical, creative and able to solve problems well through argumentation skills training.